2022
DOI: 10.3390/nu14194045
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits, Food Product Selection Attributes, Nutritional Status, and Depression in Middle-Aged and Older Adults with Dysphagia

Abstract: Dysphagia, which increases the risk of malnutrition and depression, is an important health concern. A total of 304 people aged 50 years or above (148 subjects with dysphagia and 156 non-dysphagia subjects) were recruited for this survey of dietary habits, meal product selection attributes, nutritional status, and depression. For group comparisons, chi-square tests were performed. Exploratory factor analysis was conducted for the meal product selection attributes. Correlation analyses were performed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Studies show that a higher proportion of older subjects have dysphagia (swallowing problems). It is associated with depression, malnutrition, and with a lower proportion of subjects engaging in economic activity [ 34 ]. Patients with dysphagia were found to be highly dependent on meal behavior, and were mostly not able to prepare their own meal.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that a higher proportion of older subjects have dysphagia (swallowing problems). It is associated with depression, malnutrition, and with a lower proportion of subjects engaging in economic activity [ 34 ]. Patients with dysphagia were found to be highly dependent on meal behavior, and were mostly not able to prepare their own meal.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the accuracy rate of “avoiding the consumption of viscous liquids” and “eating liquid foods is safest” is low, indicating that most of nurses have incorrect understanding of the diet of elderly people with swallowing disorders. Choosing the correct food intake is the primary task of swallowing disorder management [ 20 ]. A study [ 21 ] found that attention should be given to nutrient intake after orthopaedic spine surgery, especially cervical spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Skipping breakfast and eating alone are risk factors for depression 34,35 . Patients with dysphagia are at higher risk for depression 36 . ) Oral problems such as edentulous and periodontal disease increase the risk of depression 37 .…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%
“… 34 , 35 Patients with dysphagia are at higher risk for depression. 36 ) Oral problems such as edentulous and periodontal disease increase the risk of depression. 37 Oral diseases have psychosocial consequences.…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%